Occupational architecture – Nazi projects in Poznań - Grzeszczuk-Brendel, Hanna (City and War, 2021)
War usually causes damage and suspension of construction work, thus intensified Nazi activity in Poznań brings into focus the ideological functions of architecture. During World War II, the then capital city of Gau Wartheland was the site of numerous urban and architectural projects, as well as many new housing estates and green areas. Moreover, the occupant worked on the conversion of the former imperial castle into a Deutsches Schloss, that is Hitler’s headquarters, which were to express the Third Reich’s dominance over the conquered territories. This was also the function of residential buildings. Many of these projects were given the status of “important to military operations”, hence the architecture should be perceived as a means to secure the territorial gains, and the German settlers as colonists and occupants. The housing estates displayed features of mass construction developed with a view to post-war times and were, therefore, intended to document the ‘endless’ control of the areas incorporated into the Reich. The estates also served to transform these areas in line with Nazi ideology.